Deflation – Real Problem to be Solved or Inevitable Consequence of Globalization? : - Mudra, Martin (2016)
The aim of this paper is to examine the striking inverse co-movement of decreasing inflation rates and increasing degree of globalization in developed economies during the current wave of globalization beginning in the 1980s. Our analysis stands on theoretical identification of channels through which globalization affects inflation in developed economies and the role of monetary policy in the process. Econometric estimation of the impact of advancing globalization on the rate of inflation carried out on a sample of high-income OECD countries over the years 1980 - 2013 supports our hypothesis that advancing globalization has a significant negative impact on the rate of inflation in advanced economies.